The legitimacy of land use planning laws governing the spatial location of urban functions: an assessment in terms of the international covenant on economic, social and cultural rights (ICESCR). - Banda, Felemont Kayulayula Zilale (University of the Witwatersrand, Johannesburg, 2023)
The study's primary objective was to evaluate the legitimacy of Malawi's land use planning laws and regulations using ICESCR and Thomistic natural law frameworks. In order to achieve the primary objective, the study sought to explain the scope and nature of states parties’ obligations in the implementation of economic, social, and cultural rights in the urban space; examine the legitimacy of land use planning laws governing the spatial location of urban functions; and analyse indicators of dissonance between discursive practices and written law in the urban space. In pursuit of these objectives, the study used a doctrinal research approach. The study thus analysed legislation, rules, regulations, orders, By-laws, authoritative court decisions, and planning-related literature. The study shows that states parties to the ICESCR do not attach spatial context to the Covenant obligations. As a result, they fail to ensure that the Covenant rights are enjoyed on an equal footing in the urban space among residents of different income statuses. The study has also found that, in order for land use planning laws to be legitimate, the state shoulder the obligation to ensure that the enacted planning laws are for the common good, do not impose unfair burdens on citizens, and are enacted with authority in line with consent and social contract doctrines. Land use planning laws in Malawi do not reflect the economic realities of urban citizens. These planning laws are neo-colonialistic as they principally reflect the European colonial planning paradigm, whose objective was the appropriation of resources to benefit the White settler community in colonial territories. Such a legislative background has resulted in the dissonance between the written law and discursive practices, which has caused a crisis of the legitimacy of land use planning laws as evidenced by massive noncompliance and the state’s inability to enforce the laws in urban spaces. My central thesis demonstrates that the chaotic nature of urban development in Malawi emanates from the state’s failure to enact legitimate fair laws from the perspective of low-income urban residents who are in the majority. The thesis is significant because it has revealed that states must review their laws in good faith and that a Thomistic reading of the laws would assist in aligning them with state-party obligations under the Covenant. Moreover, the thesis highlights the importance of land use planning laws reflecting urban citizens’ socioeconomic needs, which is the principal condition precedent for the legitimacy of laws in the urban space
A research report submitted in fulfillment of the requirements for the degree of Master of Laws (by research) In the School of Law at the University of Witwatersrand, Johannesburg, 2023
Keywords: Land use; ICESCR; UCTD; SDG-15: Life on land